Cyclodextrin Chemistry and Toxicology - Isidori, Marina; Lavorgna, Margherita; Iacovino, Rosa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This is a reprint of the Special Issue "Cyclodextrin Chemistry and Toxicology". This is a collection of eleven articles and three reviews that was published in Molecules that provides an overview of the applications of cyclodextrins, implements the information regarding the use of cyclodextrins and their inclusion complexes, considering both experimental and theorists approaches and using various scientific and technological tools.